2023
DOI: 10.21203/rs.3.rs-2630342/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Knowledge and Attitudes of Medical Doctors in South Africa towards Medical Cannabis: A Qualitative Study

Abstract: Background The attitudes and perceptions of medical practitioners towards medical cannabis is important to understand. A qualitative study was conducted to examine the attitudes and knowledge of medical doctors in South Africa towards medical cannabis. Methods Twenty medical doctors were recruited for online semi-structured interviews, which were guided by predefined themes including knowledge, legislation, willingness to prescribe, and potential risks. The data collected was analyzed using thematic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…As shown by Mekrungrongwon (2022), health care providers admitted that they need training regarding medical Cannabis in at least some aspects of its legislation, like prescription of medical Cannabis or medicines with its substances or oils and extracts. In a recent publication (Audain, 2023), through an online semi-structured interview of 20 medical doctors in South Africa, it was reported that 12 of them claimed that the legislation is vague, unclear and confusing, and other 4 were even unaware of any legislation regarding medical Cannabis. In another study, it was shown that some physicians even feared the risk to their reputation if issues arose for patients to whom they prescribed medical Cannabis (Manoharan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Mekrungrongwon (2022), health care providers admitted that they need training regarding medical Cannabis in at least some aspects of its legislation, like prescription of medical Cannabis or medicines with its substances or oils and extracts. In a recent publication (Audain, 2023), through an online semi-structured interview of 20 medical doctors in South Africa, it was reported that 12 of them claimed that the legislation is vague, unclear and confusing, and other 4 were even unaware of any legislation regarding medical Cannabis. In another study, it was shown that some physicians even feared the risk to their reputation if issues arose for patients to whom they prescribed medical Cannabis (Manoharan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%